Nexus between financial accountability or transparency and corruption in parastatals in Zimbabwe: Financial accountability and corruption - Wadesango, Newman; Nhubu, Tinotenda (The Journal of Accounting and Management, 2021)
The purpose of this research was to investigate the relationship between financial accountability or transparency and corruption in parastatals using one parastatal. The research objectives outlined the quality of financial reporting, audit and budget and budgetary control. The descriptive survey research design, regression analysis was used and data was gathered through questionnaires. A total population of 24 employees including top management, accountants, auditors, HR and IT was sampled using convenience and purposive sampling. Research instruments considered for the purposes of this research are questionnaires which had 77% response rate. The data gathered was presented through bar graphs, pie charts and tables. The data accumulated was analyzed using regression analysis as a statistical method and conclusions were drawn from this. After the analysis it was revealed that financial accountability or transparency have a significant effect on corruption. The recommendations passed by the researchers included more training and experience for internal auditors and accountants. The researchers also recommended that G.M.B should take matters seriously against people who engage in corrupt activities instead of transferring them to different departments.